Innovative Use of Palm Oil Fly Ash-Based Zeolite for Zinc (II) Removal from Wastewater - Lita Darmayanti; Rodiah Rabi’ah Al Adawiyah (School of Postgraduate Studies, Diponegoro Univer, 2025)
Zinc (Zn) is a heavy metal commonly found in wastewater, with Zn (II) levels above the threshold causing health problems and environmental pollution. Though zinc is essential, excess zinc can lead to poisoning. Thus, Zn (II) must be removed before releasing water into the environment. The adsorption method is effective for controlling heavy metal pollution, with zeolite based on POFA (palm oil fly ash) as a useful adsorbent. This research aims to analyze the influence of pH, adsorbent dose, contact time, and initial concentration on POFA-based zeolite's ability to remove Zn (II). Experiments were conducted by varying pH (3, 4, 5, 6, 7), adsorbent dosage (1, 1.5, 2, 2.5, 3 g/L), contact time (5, 10, 15, 30, 60, 90, 120, 150, 180 minutes), and initial Zn (II) concentration (2, 4, 6, 8, 10, 15 mg/L). Results showed the highest Zn removal efficiency at pH 6, an adsorbent dose of 2 g/L, and a contact time of 60 minutes, achieving 98.77% removal. The Zn (II) adsorption process fits the Langmuir and Freundlich isotherms, with a maximum adsorption capacity of 28.27 mg/g. The adsorption kinetics followed a pseudo-second-order model with qe 5.04 mg/g and an adsorption rate constant of 0.197 g.mg-1.min-1.